The Degree of Students' Perception of American Idioms (Journal of Humanities and Social Sciences Research, 2023)
This study aims to investigate “EFL students Perception of American Idioms”. The problem of this study is the major points that make idioms such an obstacle to the English learners to understand the common idioms in English.  The purpose of this study is to find out the degree of perception of students since little attention is given to teaching them and there is a wide difference between British idioms and American idioms. Besides, idioms are so wide domain and it evolve many domains in life and use that makes them difficult. The data of the study has been collected by using a diagnostic test. The test consists of five questions. It has been used the statistical package for social science (SPSS) to analyze the data and show the results that the researcher has obtained from the test. The results have shown that the students face difficulty in perceiving the idiomatic expressions. It also has showed that EFL students are less exposed to idioms; this might be due to the fact that they depend on free topics presented by their teachers which may or may not include idioms. Also, students have used to memories idioms with their literal meaning without knowing their figurative meaning. According to results, the students has shown a weakness in perceiving the difference in pronunciation between American and British idioms. It is recommended that more attention be given to teaching American idioms as well as British idioms since they affect the comprehension of communication and reflect the style of life, which is neglected in our classes.